Dealing with Students Pronunciation: the “Spelling Bee” Effect - Khasanah, Uswatun; As Sabiq, Agus Husein (Universitas PGRI Adi Buana Surabaya, 2020)
Pronunciation is put on bottom list in English teaching-learning process, and students focused to learn grammar. The aim of this research was to investigate the effect of “Spelling Bee” technique towards students’ pronunciation. The researcher used the experimental method. The sample of the research was 63 students in seventh-grade MTs NU 01 Mambaul Hikmah Tegalwangi which was consist of 32 female students of seventh E as experimental class and 31 female students of seventh D as control class. The sampling technique used cluster random sampling. The instrument of the research used jumble letters and speaking test as pre-test and post-test which were analyzed using Microsoft Excel. The result of the research indicated that there was a significant difference between students’ post-test in experimental class and control class. The mean score of the post-test in the experimental class was (71.806) while the score post-test in the control class was (23.306). Besides, the result of the t-test showed that t-stat (27.125) was higher than t-table (1.688) with a degree of freedom (df) = 36 as a result Ha was accepted and H0 was rejected. It meant that the “Spelling Bee” technique had a significant influence in teaching pronunciation at seventh-grade of MTs NU 01 Mambaul Hikmah Tegalwangi. “Spelling Bee” can be an alternative technique for teachers to improve students’ pronunciation as well as their vocabulary and spelling skills.